Artikel Review : Pengelolaan Standar Pendidikan Berbasis Teknologi Informasi dan Komunikasi sebagai Upaya Peningkatan Mutu Pendidikan di Indonesia - Ahmadi, Ahmadi; Insan, Abdul; Mustari, Mohamad (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2023)
The rapid development of information technology in the current era of globalization cannot be avoided anymore its influence on the world of education. The development of technology helps learners create learning communities by using digital communication channels. In addition, the use of information and communication technology is able to accelerate effective and efficient management and education systems. The purpose of writing a review article is to describe the utilization of managing educational standards based on information and communication technology in the world of education. The method used in this study is library research. The data collection method uses the help of the internet to browse various references to books and previous research journals that are in accordance with the Management of Information and Communication Technology-Based Education Standards in relation to improving the quality of national education. The results of this study showed that the development of information and communication technology had a rapid impact on the world of education, especially in learning activities, educational administration and also on the management of educational standards in the 21st century.